Byung-Chul Han: Digital Technologies, Social Exhaustion, and the Decline of Democracy - Picchione, John (New Explorations, 2023)
Byung-Chul Han’s pivotal works display a provocative examination of digital technologies, capitalism and its commodification of life, achievement society and its pathologies. This article examines these issues in relation to the end of the disciplinary and immunological paradigm and the shift toward a neuronal model at the base of the present-day human subject and its social and political consequences. The relationship between new technologies and self-exploitation, pornographication of the ego and the disappearance of the Other is explored in conjunction with the overload of information and entropy, and an agonizing democracy.